Gerakan Tajdid: Sejarah dan Perspektif Masa Kini - Ab. Majid, Mohamad Kamil (Jurnal Usuluddin, 1996)
This paper attempts to discuss the meaning of tajdid, to trace its development and to suggest its form and practice in the days of sahabat and tabiin. The discussion also covers tajdid hadari, i.e. globalization of tajdid as it is taking place at the moment and the challenges facing it in the form of ideas and practices from tajdid in politic and dakwah. It is suggested that tajdid should be moved and led by a multi-disciplinary well-informed leader especially in this modern society, and institutions of higher learning should estimate themselves to contribute to this leading role.